The Role of Employee Multitasking Mediation in the Relationship Between High Performance Work Systems, Employee Performance and Compensation - An Nisa, Milenia; Baskara, Ika (International Journal of Economics (IJEC), 2024)
A study has shown that there may be a gap in the mediating role of employee multitasking in the relationship between high-performance work systems, employee performance and compensation. Data from target employees was collected using a Google Form questionnaire. A total of 112 employee representatives from companies at PT Bina Karya Prima in the Jakarta and Bekasi areas, Indonesia took part in this research, the sample was selected using the purposive sampling method. The author used the SMART-PLS Structural Equation Model (SEM) to test the research model, and carried out validity and reliability tests using SPSS factor analysis. The findings of this research reveal that employee multitasking has a positive and significant effect on high-performance work systems and employee performance. Finally, there is a control variable, namely compensation. Compensation has a positive and significant effect on high-performance work systems and employee performance. Finally, we found that employee multitasking mediates the positive and significant relationship between high-performance work systems, employee performance and the relationship between high-performance work systems and employee performance on compensation control variables. To unlock the mystery surrounding the relationship between high-performance work systems and employee performance, this research includes the mediating role of employee multitasking and develops a new theoretical framework, namely compensation.